Changing Places? : Flexibility, Lifelong Learning and a Learning Society. - Edwards, Richard, 1956 July 2- (Routledge, 1997)
This books looks at how the notion of the learning society has developed over the years, and how, and why, flexibility has become a more central concept in much policy and academic debate.